Reconstructing the paleobiogeographic history of the lanner falcon (Falco biarmicus) in the Mediterranean basin: towards a future perspective for its conservation - Giovanni Leonardi; Luke J. Sutton; Haralambos Alivizatos; Alessandro Andreotti; Lale Aktay-Sözüer; Ergün Bacak; Sercan Bilgin; Albara Binothman; Atanas Grozdanov; Umut Güngör; Mátyás Prommer; Lavrentios Sidiropoulos; et al. (Ornithology Research, 2024)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Biodegradability of legacy crude oil contamination in Gulf War damaged groundwater wells in Northern Kuwait - Melanie C. Bruckberger; Matthew J. Morgan; Tom Walsh; Trevor P. Bastow; Henning Prommer; Amitabha Mukhopadhyay; Anna H. Kaksonen; Greg Davis; Geoffrey J. Puzon (Biodegradation, 2019)

The effects of classic altitude training on hemoglobin mass in swimmers - N. B. Wachsmuth; C. Völzke; N. Prommer; A. Schmidt-Trucksäss; F. Frese; O. Spahl; A. Eastwood; J. Stray-Gundersen; W. Schmidt (European Journal of Applied Physiology, 2013)

Influence of altitude training modality on performance and total haemoglobin mass in elite swimmers - Clare E. Gough; Philo U. Saunders; John Fowlie; Bernard Savage; David B. Pyne; Judith M. Anson; Nadine Wachsmuth; Nicole Prommer; Christopher J. Gore (European Journal of Applied Physiology, 2012)